-(8x+1)-2=8-7x

Simple and best practice solution for -(8x+1)-2=8-7x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(8x+1)-2=8-7x equation:


Simplifying
-1(8x + 1) + -2 = 8 + -7x

Reorder the terms:
-1(1 + 8x) + -2 = 8 + -7x
(1 * -1 + 8x * -1) + -2 = 8 + -7x
(-1 + -8x) + -2 = 8 + -7x

Reorder the terms:
-1 + -2 + -8x = 8 + -7x

Combine like terms: -1 + -2 = -3
-3 + -8x = 8 + -7x

Solving
-3 + -8x = 8 + -7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '7x' to each side of the equation.
-3 + -8x + 7x = 8 + -7x + 7x

Combine like terms: -8x + 7x = -1x
-3 + -1x = 8 + -7x + 7x

Combine like terms: -7x + 7x = 0
-3 + -1x = 8 + 0
-3 + -1x = 8

Add '3' to each side of the equation.
-3 + 3 + -1x = 8 + 3

Combine like terms: -3 + 3 = 0
0 + -1x = 8 + 3
-1x = 8 + 3

Combine like terms: 8 + 3 = 11
-1x = 11

Divide each side by '-1'.
x = -11

Simplifying
x = -11

See similar equations:

| -7(2b+4)+(15b-7)=0 | | 12p^4-92p^3-144p^2=0 | | m-8m-3m-1= | | 45*5/9 | | 2x^4=50 | | x+16=4x+4 | | 4x+3/2=11 | | 4(3)+y=11 | | 4x-7y=11fory | | 5.9q-2.2-5.3q=-0.4q-4.3 | | 42n^3+6n^2=0 | | 2(-2)-3x=5 | | 5x^2-5x^2= | | N^2-8n=-15 | | 2x^2-21x=11 | | 12x^2+51x+45= | | N^2-8k-3=-3-5k^2 | | x/5+x/7=6/5 | | x^2+16=36+x^2+4 | | -15p^2+17p+4= | | 2(5x+5)-3= | | 3p+4m-6-p+3m+5p-11-m= | | 2x+5(3/2)=16 | | 8x^2-16x-280= | | 2x^2+12x=3x-9 | | 1/x=0.01 | | 126=(x+2)(2x) | | 6n^2+9+12n-6-24=0 | | 2(-3)+5(x)=16 | | y-20n=6y | | 2a+8=2 | | 2(x+3)+4=20 |

Equations solver categories